Distance learning reforming swedish experience implementation into ukrainian higher education system - Ageicheva, Anna; Komarova, Oleksandra; Babash, Larysa (НТУ "ХПИ", 2018)
The article deals with the conceptual ideas of distance education in the European Higher Education Area and future prospects definition in distance learning implementation into higher education system of Ukraine. Development system of higher education and distance learning development stages are analyzed. The main goal of creating distance education in Ukraine is to increase the level of education of the society and the quality of education, as well as the formation of a single educational space. It is necessary to address such major challenges as the formation of legal, organizational, teaching, information and telecommunications, logistics, personnel, economic and financial support. The development of distance education will not only provide our population access to quality education, but also provide an opportunity to take a place on the global education market.

Статья посвящена исследованию концептуальных идей дистанционного образования в Европейском пространстве высшего образования и определению дальнейших перспектив развития отечественной практики внедрения дистанционного обучения в систему высшего образования Украины. Проанализировано систему развития высшего образования и этапы развития дистанционного обучения.
Реформирование шведского опыта дистанционного обучение в украинскую систему высшего образования
Keywords: communication technology; information technology; reforming trends; distance learning; информационно-коммуникационные технологии; тенденции реформирования